MORAL EDUCATION FOR EARLY CHILDHOOD AT SHEJA SCHOOL USING THE ROLE MODEL METHOD - Sigalingging, Sery (Jurnal Review Pendidikan dan Pengajaran, 2024)
This study was motivated by the low effectiveness of teachers in providing moral education to support the moral development of early childhood children in Group B at SSHEJA School. The aim of this research is to enhance the moral development of children through the role model method at PAUD SHEJA School in Bukit Mengkirai Village, Gebang Subdistrict, Langkat Regency. The subjects of this study were 10 children at PAUD SHEJA School. The focus of this research is to investigate whether the role model method can improve the moral development aspects of children at PAUD SHEJA School. The method used in this study was direct instruction with the classroom action research (CAR) model, which involved planning, implementing actions, observing learning outcomes, and reflecting over three cycles. The data analysis results indicate that the observation and assessment of the learning plan yielded the following outcomes: first, Cycle I achieved a score of 46.6% from 3 categories and 9 observational aspects; second, cycle II achieved a score of 70% from 3 categories and 13 observational aspects, categorized as moderate; third, cycle III achieved a score of 90% from 3 categories and 13 observational aspects, categorized as good. The results of the learning implementation from the activities of teachers and children were: cycle I obtained a score of 43%, cycle II achieved a score of 73%, categorized as moderate, cycle III obtained a score of 86%, categorized as good. The assessment of learning outcomes, specifically the improvement in children's moral development, showed: cycle I reached a percentage of 50%, cycle II achieved a class percentage of 61.4%, cycle III reached a percentage of 85.7%. Based on the research findings and discussion, it can be concluded that the moral development of children in Group B at PAUD SHEJA School, Bukit Mengkirai Village, Gebang Subdistrict, Langkat Regency, can be enhanced through the role model method. Utilizing the role model method can effectively strengthen the moral development of children, resulting in optimal improvement. It is recommended that future researchers explore and develop other teaching methods or instructional media that could be more effective in enhancing learning outcomes.